Plasma Levels of CGRP During a 2-h Infusion of VIP in Healthy Volunteers and Patients With Migraine: An Exploratory Study - Pellesi, Lanfranco; Al-Karagholi, Mohammad Al-Mahdi; De Icco, Roberto; Chaudhry, Basit Ali; Lopez, Cristina Lopez; Snellman, Josefin; Hannibal, Jens; Amin, Faisal Mohammad; Ashina, Messoud (Frontiers in Neurology, 2022)
Background: The activation of perivascular fibers and the consequent release of vasoactive peptides, including the vasoactive intestinal polypeptide (VIP), play a role in migraine pathogenesis. A 2-hour infusion of VIP provoked migraine, but the mechanisms remain unknown. We investigated whether 2-hour infusion of VIP caused alterations in plasma levels of the calcitonin gene-related peptide (CGRP) and whether any changes might be related to the induced migraine attacks. Methods: We enrolled individuals with episodic migraine without aura and healthy participants to randomly receive a 2-hour infusion of either VIP (8 pmol/kg/min) or placebo (sterile saline) in two randomized, placebo-controlled crossover trials. We collected clinical data and measured plasma levels of VIP and CGRP at fixed time points: at baseline (T0) and every 30 min, until 180 min (T180) after the start of the infusion. Results: Blood samples were collected from migraine patients (n = 19) and healthy individuals (n = 12). During VIP infusion, mixed effects analysis revealed a significant increase in plasma CGRP (p = 0.027) at T30 (vs. T180, adjusted p value = 0.039) and T60 (vs. T180, adjusted p value = 0.027) in patients with migraine. We found no increase in plasma CGRP during VIP-induced migraine attacks (p = 0.219). In healthy individuals, there was no increase in plasma CGRP during VIP (p = 0.205) or placebo (p = 0.428) days. Conclusion: Plasma CGRP was elevated in patients with migraine during a prolonged infusion of VIP, but these alterations were not associated with VIP-induced migraine attacks. Given the exploratory design of our study, further investigations are needed to clarify the role of CGRP in VIP-induced migraine.